Limited domestic introgression in a final refuge of the wild pigeon - Smith, W; Sendell-Price, AT; Fayet, AL; Jezierski, MT; Sheldon, BC; Kelly, S; Turnbull, LA; Clegg, SM; Et al (Cell Press, 2022)
Domesticated animals have been culturally and economically important throughout history. Many of their ancestral lineages are extinct or genetically endangered following hybridization with domesticated relatives. Consequently, they have been understudied compared to the ancestral lineages of domestic plants. The domestic pigeon Columba livia, which was pivotal in Darwin’s studies, has maintained outsized cultural significance. Its role as a model organism spans the fields of behavior, genetics, and evolution. Domestic pigeons have hybridized with their progenitor, the Rock Dove, rendering the latter of dubious genetic status. Here, we use genomic and morphological data from the putative Rock Doves of the British Isles to identify relictual undomesticated populations. We reveal that Outer Hebridean Rock Doves have experienced minimal levels of introgression. Our results outline the contemporary status of these wild pigeons, highlighting the role of hybridization in the homogenization of genetic lineages.